Advances in grassland research in the Mediterranean region of Chile - Del Pozo A.; Ovalle C. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The Central Zone of Chile, the only part of South America that presents a Mediterranean climate, has about 5 million hectares of pasture. A large proportion are annual species from the Mediterranean Basin. This article presents a summary of the results of 20 years of research carried out in order to improve productivity of livestock production systems and contribute to the rehabilitation of these degraded agroecosystems. The studies have considered both the collection and domestication of naturalized annual legumes in Chile (Medicago polymorpha) and the assessment of several accessions and cultivars of annual legumes of the genus Trifolium, Medicago, Ornithopis and Biserrula. The works have also considered the design and assessment of pasture mixtures, the evaluation of N fixation in addition to the integration of legumes in crop rotations and as cover crop in vineyards and orchards. Evaluations were performed in a gradient of rainfall between 600 and 1000 annual rainfall on volcanic soils (Andisols) and Entisols derived from granitic rocks. The productivity and persistence of B. pelecinus in the interior dryland and O. compressus in the Andean foothill are clearly superior to other annual legumes (M. polymorpha or T. subterraneum) seeded in those areas. The use of legume mixture is also highly recommended due to their higher productivity and persistence compared to monospecific pastures. The amount of N2 fixed by annual legumes is closely related to the shoot dry matter production of the pasture, and the rate is 18-20 kg shoot N fixed per ton shoot DM accumulated. Finally, annual legumes contribute to the N nutrition of wheat or grapevines in a Mediterranean environment.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)